THE ROLE OF PERSONALITY ON QUALITY OF LIFE AMONG TYPE 2 DIABETES PATIENTS - IBRAHIM, NORHAYATI (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes is one of the silent killer because many diabetic patients are unaware of their disease, symptoms and the complications of the disease. Diseases and certain personality traits have been associated with behaviors that may lead to negative health outcomes. Hence, the objective of this study is to determine the correlation between personality and the quality of life among type 2 diabetic patients. A total of 200 type 2 diabetic patients were selected for this study. Patients were surveyed using validated questionnaires – Short Form 36 (SF-36) to assess the health related quality of life and Big Five Inventory (BFI) to assess the personality traits of patients. The findings of this study showed that most of the sub-domains of the Big-Five Inventory were positively correlated with the sub-domains of Health related quality of life (HRQOL) except for the Neuroticism sub-domain, which correlated negatively with the sub-domain of HRQOL. The study also found that personality contributed 14.3% of the variation to the physical component summary (PCS) domain, while 24.3% of the variation contributed to the Mental component summary (MCS) domain of HRQOL. Therefore, a better understanding of the importance of patient's personality among type 2 diabetic patients is fundamental to improving their health related quality of life.